Effects of Intestinal FXR-Related Molecules on Intestinal Mucosal Barriers in Biliary Tract Obstruction - Yan, Meng; Hou, Li; Cai, Yaoyao; Wang, Hanfei; Ma, Yujun; Geng, Qiming; Jiang, Weiwei; Tang, Weibing (Frontiers in Pharmacology, 2022)
Background: The farnesoid X receptor (FXR) is a key factor regulating hepatic bile acid synthesis and enterohepatic circulation. Repression of bile acid synthesis by the FXR is a potential strategy for treating cholestatic liver disease. However, the role of intestinal FXR on the intestinal barrier and intestinal microbiota needs further investigation. Materials: Intestinal tissues were collected from patients with biliary atresia or without hepatobiliary disease. Then, intestinal mRNA levels of FXR-related molecules were determined. To investigate the effect of FXR activation, bile-duct-ligation rats were treated with obeticholic acid [OCA (5 mg/kg/day)] or vehicle (0.5% methyl cellulose) per oral gavage for 14 days. The mRNA levels of intestinal FXR, SHP, TNF-α, FGF15 and bile acid transporter levels were determined. In addition, the intestinal permeability, morphologic changes, and composition of the intestinal microbiota were evaluated. Gut Microbiome was determined by 16S rDNA MiSeq sequencing, and functional profiling of microbial communities was predicted with BugBase and PICRUSt2. Finally, the role of OCA in injured intestinal epithelial cell apoptosis and proliferation was examined by pretreatment with lipopolysaccharide (LPS) in Caco-2 cells. Results: The downstream of the FXR in ileum tissues was inhibited in biliary obstruction. Activation of the FXR signaling pathway by OCA significantly reduced liver fibrosis and intestinal inflammation, improved intestinal microbiota, and protected intestinal mucosa in BDL rats. OCA also altered the functional capacities of ileum microbiota in BDL rats. Significant differences existed between the controls and BDL rats, which were attenuated by OCA in the alpha diversity analysis. Principal coordinates analysis showed that microbial communities in BDL rats clustered separately from controls, and OCA treatment attenuated the distinction. Bugbase and PICRUSt2 analysis showed that OCA changed the composition and structure of the intestinal microbiota and improved the metabolic function of the intestinal microbiota by increasing the relative abundance of beneficial bacteria and reducing the relative abundance of harmful bacteria. Moreover, OCA reduced the apoptosis induced by LPS in Caco-2 cells. Conclusion: The FXR agonist, OCA, activates the intestinal FXR signaling pathway and improves the composition and structure of the intestinal microbiota and intestinal barrier in BDL rats.